Green Economy, Trade, and Consumers – Interactions in European Green Transition - Dushkova, Miglena; Kostov, Ivo (Geomatics and Environmental Engineering, 2025)
This article presents a current and significant problem by exploring the main problems of the European Green Transition; the authors discuss these in two aspects: first, the goals of the Green Transition as one of the European Union’s strategic priorities – the goals, achievements, and possible risks that face the European Union’s green policies are discussed. The second aspect of the study is the authors’ attempt to reveal and comment on the role of trade and consumers as a tool that works in favor of the Green Transition – specifically, those that are included in European Union documents such as the Green Deal and the Circular Economy Action Plan. The definition of the problem is based on the understanding that, on the one hand, trade as an economic sector is developing most dynamically and on a large scale, making Sector G the largest set of enterprises among all of the sectors that carry out economic activities in the EU (including Bulgaria). On the other hand, trade as a business activity is closely linked to consumers; it actively interacts with them and, therefore, has a significant impact on their behaviors (including their impact on the environment). In practice, it is impossible to achieve the green goals without the connection and interaction “trade-consumers”; in addition to being aimed at achieving a modern, resource-efficient, and competitive EU economy, these reflect the Union’s aspiration to protect its people’s health and increase their collective well-being.